2016
DOI: 10.1093/gbe/evw227
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Intracellular “Ca.Endomicrobium Trichonymphae” Genomovars Illuminates the Requirement and Decay of Defense Systems against Foreign DNA

Abstract: “Candidatus Endomicrobium trichonymphae” (Bacteria; Elusimicrobia) is an obligate intracellular symbiont of the cellulolytic protist genus Trichonympha in the termite gut. A previous genome analysis of “Ca. Endomicrobium trichonymphae” phylotype Rs-D17 (genomovar Ri2008), obtained from a Trichonympha agilis cell in the gut of the termite Reticulitermes speratus, revealed that its genome is small (1.1 Mb) and contains many pseudogenes; it is in the course of reductive genome evolution. Here we report the comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
33
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 38 publications
2
33
1
Order By: Relevance
“…The NkOx7-01 and NkOx7-02 genomes encoded CRISPR-Cas systems. CRISPR loci have been found in the genomes of several other bacterial species from the termite gut [43,[65][66][67], and we also found CRISPR-Cas systems widely in other known genomes of 'Margulisbacteria' (data not shown). The absence of cytochrome oxidase, catalase and superoxide dismutase indicated that they are strict anaerobes, and the presence of rubrerythrin and rubredoxin may facilitate the survival of these bacteria during oxidative stress [68].…”
Section: Discussionsupporting
confidence: 58%
“…The NkOx7-01 and NkOx7-02 genomes encoded CRISPR-Cas systems. CRISPR loci have been found in the genomes of several other bacterial species from the termite gut [43,[65][66][67], and we also found CRISPR-Cas systems widely in other known genomes of 'Margulisbacteria' (data not shown). The absence of cytochrome oxidase, catalase and superoxide dismutase indicated that they are strict anaerobes, and the presence of rubrerythrin and rubredoxin may facilitate the survival of these bacteria during oxidative stress [68].…”
Section: Discussionsupporting
confidence: 58%
“…Nevertheless, the presence of defense systems against foreign DNA in "Ca. Endomicrobium trichonymphae" (32) suggests that endosymbionts of termite gut flagellates, unlike the obligately intracellular bacteria colonizing insect tissues (2), are not entirely cut off from gene flow in their intracellular habitat.…”
Section: Discussionmentioning
confidence: 99%
“…The complete genome sequences of ‘ Candidatus Endomicrobium trichonymphae’ phylotype Rs‐D17 were obtained from bacterial populations within the cells of the protist Trichonympha agilis from the gut of the termite Reticulitermes speratus (Hongoh et al ., ; Izawa et al ., ). Genome analyses suggested that the endosymbionts are specialized to synthesize amino acids and cofactors and may provide nitrogenous compounds to the host protist and termite (Hongoh et al ., ; Izawa et al ., ). Considering the abundance and ubiquity of Endomicrobium endosymbionts in the gut of lower termites, they may play important roles in the termite gut symbiotic system.…”
Section: Introductionmentioning
confidence: 97%